Mitral Valve Papillary Fibroelastoma as the Cause of Ischemic Stroke in a Young Patient: A Case Report - Vasconcelos, Milena Miranda [UNESP] (2021)
Objective: Rare disease Background: Primary cardiac tumors represent less than 5% of total cardiac tumors. Fibroelastoma is a rare benign cardiac tumor that is usually asymptomatic but is acknowledged for its emboligenic potential for causing cardiac, neurological, and vascular symptoms and increasing patient morbidity and mortality. Case Report: This report describes the clinical case of a 27-year-old woman who entered the Emergency Department with motor aphasia and hemiparesis in the right dimidium. A brain computed tomography scan was performed at admission, which showed left frontal-parietal hypodensity. The diagnosis of ischemic stroke was made, but cerebral reperfusion therapy with intravenous recombinant tissue plasminogen activator was not instituted due to the time that had passed since ictus (15 h 40 min). On the first day of hospitalization, the patient had a fever, with no apparent infectious cause. She underwent transthoracic echocardiogram that showed a sessile, isoechoic mass adhered to the atrial surface of the anterior mitral valve leaflet, measuring 6.8x5.5 mm. Antibiotic therapy with ceftriaxone and gentamicin was initiated due to the initial diagnosis of infective endocarditis. Three blood culture samples had negative results. Given a differential diagnosis of fibroelastoma, transesophageal echocardiography and cardiac resonance imaging were performed, and the findings were compatible with a diagnosis of mitral valve fibroelastoma. After clinical discussion, the patient was referred to cardiac surgery and underwent tumor resection with anatomopathological diagnosis of papillary fibroelastoma of the heart valve. Conclusions: Young patients with ischemic stroke must be investigated with transthoracic and transesophageal echocardiograms. Papillary fibroelastoma is potential cause of ischemic stroke in young patients, and surgical resection is curative and has excellent prognosis.